2015
DOI: 10.18775/ijied.1849-7551-7020.2015.14.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Unethical Advertising, Misleading Information or Deceptive Advertising on Customer Purchasing Intention with Mediating Effect of Word of Mouth: Case of Pakistan

Abstract: Purpose -This paper aims to study the effect of Unethical advertising, misleading information or deception and stereotyping advertising impact on Customer purchase intention with mediating effect of word-of-mouth (WOM) in Pakistan. Based on variables, the authors tried to identify the effects of each variable to customer satisfaction. Data were collected through field research (questionnaire) among 600 Respondent who have their own different levels and fields like, Employee, students, and common people from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Previous research found that consumers' sureness is based on previous consumers' opinions as well as understandings more than advertisements of marketers (Sen & Lerman, 2007). The advertisements begin to lose their capacity on buyers because of reliability issues (Ullah & Hussain, 2015). On the off chance that the links amongst the sender as well as the beneficiary of the data are durable, the validity of the data will be sufficiently high for the collector to have confidence in that the dealer is dependable (Brown & Reingen, 1987).…”
Section: Anthology Of the Previous Study A Word Of Mouth To Electronmentioning
confidence: 99%
“…Previous research found that consumers' sureness is based on previous consumers' opinions as well as understandings more than advertisements of marketers (Sen & Lerman, 2007). The advertisements begin to lose their capacity on buyers because of reliability issues (Ullah & Hussain, 2015). On the off chance that the links amongst the sender as well as the beneficiary of the data are durable, the validity of the data will be sufficiently high for the collector to have confidence in that the dealer is dependable (Brown & Reingen, 1987).…”
Section: Anthology Of the Previous Study A Word Of Mouth To Electronmentioning
confidence: 99%
“…Usually the first perception of a new advertisement is surface, inaccurate and not fully understood [25,30,[34][35][36]. Although the new information is not added, subsequent presentations of this ad lead to the fact that its content becomes more conscious, understandable, more deeply perceived.…”
Section: Description Of the Information Approach In The Advertising Rmentioning
confidence: 99%
“…According to Ullah, Najeeb & Hussain, Mustansar, (2015), advertising is one of the most integral parts of a business entity that integrates several key fields, including marketing, communications, consumerism, economics, education, social and religious affairs (Kamassi, A.,2019, Abdullah, Kalthom & Haque, Ahasanul & Ahmed, Faruk & Shafiq, Ali., 2019Shafiq, A., Haque, A., & Abdullah, K., 2016). It has different objectives beyond its practice; to inform, educate, convince, persuade, remind, offer, and profit (Safira, Anya, 2017;Busen & Mustaffa, 2014).…”
Section: Introductionmentioning
confidence: 99%